THE EFFECT OF BRAND EQUITY ON CUSTOMER REVISIT INTENTION TO FAST-FOOD RESTAURANT IN MALAYSIA - Fairuz Abd Hakim; Suria Sulaiman; Noraslinda Mohd Said; Faizatul Khadijah Md Zin (International Journal of Accounting, Finance and Business, 2022)
The study examined the effect of brand equity on customer revisits intention towardfast-food restaurants in Malaysia. Further, the study explored the relationship between brandawareness, brand association, perceived quality, and brand loyalty on customer revisitintention using the theory of reasoned action (TRA). A survey was conducted using onlinequestionnaires involving 388 respondents who consumed fast-food in Malaysia. Using SPSS,descriptive and correlation analyses were used to analyse the data of this study. Findingsrevealed that three variables positively correlate with customer revisit intention. Brand loyaltyshows the strongest impact that led customer to revisit to the fast-food restaurant. The resultsare aligned with previous research that stated brand loyalty is the most critical determinantaffecting customers’ revisit intention to the restaurants. Moreover, this research contributed tothe existing body of knowledge in the field of brand management. Finally, the findings of thisstudy can be used by restaurateurs as a reference for focusing on and managing their brandequity. In line with the study, future researchers were given implications and recommendations.